علاقة الكفاءة الانفعالية بتنظيم الذات لدى طلبة الجامعة - حسين امال اسماعيل (Journal of College of Education, 2018)
The objective of the research is to identify the emotional efficiency and self-organization, and what is the relationship between them and the students of the university. In order to verify this, the researchers adopted the measure of emotional competence of Idris 2014, which consists of (41) In the final form. After ascertaining the cykometric properties of the two research fields according to the sample of 400 students, they were chosen in a random stratified manner. The results showed that the members of the sample have an emotional efficiency, which in turn enhanced the self-organization of the students through the same reality as the student and his conviction in his social and cognitive environment, and also that the members of the research sample have a self-regulation through the organization of psychological and emotional conditions, values ​​and traditions, The existence of a positive positive correlation between the emotional efficiency and self-organization of the students. This is due to the students’ interest in their emotions and information that are consistent with their psychological and psychological needs in a manner consistent with the educational situation He has the ability to control himself and to understand the consequences of things and he recalls in his mind all the possible consequences of his actions in the future, and on this basis can build his behavior and actions according to the plan is formulated and drawn on the basis of what he expects success and conciliation of his work in the distant future This person can derive his ability to control and control the emotions and behavior of the assessment of things based on the balance of results and scrutiny, and based on the results of the current research has been reached some recommendations and proposals for the future.